Utilizing scattering to further enhance integrating cavity-enhanced spectroscopy. Issue 1 (2nd January 2016) - Bixler, Joel N.; Winkler, Chase A.; Hokr, Brett H.; Mason, John D.; Yakovlev, Vladislav V.
Abstract : Spectroscopic optical characterization and identification of molecular structures and complex systems would greatly benefit from new technologies capable of analyzing molecular species in small quantities with maximum sensitivity and specificity. Integrating cavity-enhanced spectroscopy has recently been shown as a viable tool for achieving this goal. This technique could greatly benefit from methods for further enhancing the desired spectroscopic signal, allowing for lower detection limits. Here, we present a simple method to further enhance fluorescence signal generated inside an integrating cavity by introducing additional scattering to the sample of interest.